Opinions of Social Studies Teachers on Information Literacy - Turgut, Tuğba; Kaymakci, Selahattin (Kafkas Üniversitesi, 2022)
Information literacy is a versatile type of literacy that includes the ability to acquire, evaluate and use information, which can be described as an individual's information skills. At this point, the necessity for students to have information literacy skills in the social studies course, which is an important primary and secondary school course in raising active citizens, gains importance. It is obvious that social studies teachers have important duties for students to acquire these skills. The aim of this research is to reveal the opinions of social studies teachers about information literacy. In the research, the phenomenology method was used within the scope of qualitative methodology. The study group of the research consists of 44 social studies teachers working in public institutions in the 2019-2020 academic year. In the study, a structured interview form developed by the researchers was used as a data collection tool. The obtained data were analyzed through content analysis. As a result of the research, it was seen that the participants were theoretically aware of information literacy. In addition, the participants pointed out that the students are insufficient in terms of information literacy and that the reason for this situation is the lack of resources and the insufficient physical conditions of the schools, and they emphasized that the school environment should have sufficient equipment in order to raise information literate individuals. Based on the research findings, it is thought that studies examining the information literacy levels of students should be increased in terms of quantity and quality. Research should be conducted on the characteristics that appropriate learning environments should have in order to raise information literate students.

Bilgi okuryazarlığı bireyin bilgi becerileri olarak nitelendirilebilecek bilgi edinme, değerlendirme ve kullanma yetilerini içeren çok yönlü bir okuryazarlık türüdür. Bu noktada etkin vatandaş yetiştirmede önemli bir ilkokul ve ortaokul dersi olan sosyal bilgiler dersinde öğrencilerin bilgi okuryazarlığı becerilerine sahip olması gerekliliği önem kazanmaktadır. Öğrencilerin söz konusu becerileri kazanmasında ise sosyal bilgiler öğretmenlerine önemli görevlerin düştüğü aşikardır. Bu araştırmanın amacı, sosyal bilgiler öğretmenlerinin bilgi okuryazarlığına ilişkin görüşlerini ortaya koymaktır. Araştırmada nitel metodoloji kapsamında olgubilim yöntemi kullanılmıştır. Araştırmanın çalışma grubunu 2019-2020 eğitim öğretim yılında resmî kurumlarda görev yapan toplam 44 sosyal bilgiler öğretmeni oluşturmaktadır. Araştırmada veri toplama aracı olarak araştırmacılar tarafından geliştirilen yapılandırılmış görüşme formu kullanılmıştır. Elde edilen veriler içerik analizi aracılığıyla çözümlenmiştir. Araştırma sonucunda katılımcıların bilgi okuryazarlığı konusunda kuramsal olarak farkındalık sahibi oldukları görülmüştür. Buna ilaveten katılımcılar öğrencilerin bilgi okuryazarlığı açısından yetersiz olduğunu ve bu durumun nedeni olarak da kaynak sıkıntısını ve okulların fiziki şartlarının yetersiz olmasını göstermişler, bilgi okuryazarı bireylerin yetiştirilebilmesi için okul ortamının yeterli donanıma sahip olması gerektiğini vurgulamışlardır. Araştırma bulgularına dayalı olarak öğrencilerin bilgi okuryazarlık düzeylerini inceleyen araştırmaların nicelik ve nitelik bakımından artırılması gerektiği düşünülmektedir. Bilgi okuryazar öğrencilerin yetiştirilmesi için uygun öğrenme ortamlarının sahip olması gereken özelliklerin neler olması gerektiğine ilişkin araştırmalar yapılmalıdır.
Keywords: Alan Eğitimleri; Social studies; information literacy; teacher; Sosyal bilgiler; bilgi okuryazarlığı; öğretmen; Other Fields of Education